2018
DOI: 10.3390/ijms19041118
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Protects against Lung Fibrosis by Regulating the Hippo/YAP Pathway

Abstract: Idiopathic pulmonary fibrosis (IPF) is a progressive, fibrotic interstitial pneumonia with high mortality. Melatonin, a hormone predominantly secreted by the pineal gland, has been reported to participate in the process of IPF. However, the mechanisms underlying the effect of melatonin in pulmonary fibrosis have not been elucidated to date. This study was designed to evaluate the anti-fibrotic role of melatonin in pulmonary fibrosis and to elucidate the potential mechanisms. We observed that melatonin markedly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 39 publications
2
40
0
Order By: Relevance
“…The role of melatonin antioxidant properties in the prevention of COVID-19 post-infection complications should be addressed with no delay. Melatonin's ability to protect patients from pulmonary fibrosis through the Hippo/ YAP pathway has already been shown [99]. Considering that millions of people can be infected with COVID-19, while only several tens of thousands were with SARS-CoV-1, applying melatonin to prevent pulmonary fibrosis may be even more important than mitigating the acute SARS-CoV-2 infection per se.…”
Section: Melatonin As a Vaccine Adjuvant And Antiviral Immune Stimulantmentioning
confidence: 99%
“…The role of melatonin antioxidant properties in the prevention of COVID-19 post-infection complications should be addressed with no delay. Melatonin's ability to protect patients from pulmonary fibrosis through the Hippo/ YAP pathway has already been shown [99]. Considering that millions of people can be infected with COVID-19, while only several tens of thousands were with SARS-CoV-1, applying melatonin to prevent pulmonary fibrosis may be even more important than mitigating the acute SARS-CoV-2 infection per se.…”
Section: Melatonin As a Vaccine Adjuvant And Antiviral Immune Stimulantmentioning
confidence: 99%
“…Yes-associated protein (YAP) is a key downstream effector protein of Hippo. In patients with IPF, the activity of YAP increased, and the interaction of YAP and mTOR/p-S6 signaling pathways induced cell proliferation and migration, and inhibited epithelial cell differentiation [52].It has been shown that melatonin attenuated TGF-β1-induced brogenesis in pulmonary broblasts by activating the Hippo pathway and then promoting nuclear translocation and increasing the inactivation and degeneration of YAP1 in the cytoplasm [53].…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin alleviated myocardial fibrosis in animal models of myocardial infarction [24], pulmonary hypertension [25], and chronic intermittent hypoxia [26]. Bleomycin-induced experimental lung fibrosis was also attenuated by treatment with melatonin [27]. In addition, melatonin has been shown to attenuate kidney fibrosis induced by CCl4 [28], unilateral ureteral obstruction [29], or diabetes [30].…”
Section: Discussionmentioning
confidence: 99%